On live load impact factors for railroad bridges. Issue 4 (2nd October 2019) - Jacobs, David W.; Malla, Ramesh B.
ABSTRACT: Dynamic loads crossing a bridge cause a structural response greater than if the same loads were static, a fact that has been known to structural engineers for over 125 years. This review paper presents a history of the evolution of railroad bridge impact formulas. Most non-North American countries operate passenger trains at much higher speeds than in North America. In the US, hundreds of very old open deck bridges will eventually likely be required to carry faster trains. This raises the question of what effects higher speeds will have on these bridges. What factors need to be considered in the upgrading of existing open deck bridges to accommodate newer and higher speed train equipment? A comparison of how dynamic impact factors are computed in countries around the world has been presented. Also examined are the differences and reasons between the impact requirements of North American railroads and European and Asian railroads.